PENGARUH RESIKO BISNIS, PERTUMBUHAN PENJUALAN DAN STRUKTUR MODAL TERHADAP PROFITABILITY PADA PERUSAHAAN MANUFAKTUR - Tristiyan, Dicko Ferdi; Marlina, Marlina (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2014)
This study aimed to determine the effect of business risk, growth in sales and profitability of the company's capital structure in a manufacturing company engaged in the various industries that are listed in the Indonesia Stock Exchange (IDX).The data in this study used secondary data from annual reports (annual reports) are available in the companies listed on the Indonesia Stock Exchange (IDX). Data taken in the form of balance sheet and profit and loss statements and notes of financial statements, which are then analyzed using multiple linear regression analysis that should be a classic assumptions using SPSS, while the t test was used to test and F test.From the analysis and the use of hypothesis on the data available in the company based on the F test found a significant effect between business risk, sales growth and capital structure on profitability. And based on the results of t-test also found that business risk is not significant effect on profitability, sales growth no significant effect on profitability, and capital structure significantly influence profitability.